Role of Protein Kinase CK2 in Aberrant Lipid Metabolism in Cancer - Barbara Guerra; Olaf-Georg Issinger (MDPI AG, 2020)
Uncontrolled proliferation is a feature defining cancer and it is linked to the ability of cancer cells to effectively adapt their metabolic needs in response to a harsh tumor environment. Metabolic reprogramming is considered a hallmark of cancer and includes increased glucose uptake and processing, and increased glutamine utilization, but also the deregulation of lipid and cholesterol-associated signal transduction, as highlighted in recent years. In the first part of the review, we will (i) provide an overview of the major types of lipids found in eukaryotic cells and their importance as mediators of intracellular signaling pathways (ii) analyze the main metabolic changes occurring in cancer development and the role of oncogenic signaling in supporting aberrant lipid metabolism and (iii) discuss combination strategies as powerful new approaches to cancer treatment. The second part of the review will address the emerging role of CK2, a conserved serine/threonine protein kinase, in lipid homeostasis with an emphasis regarding its function in lipogenesis and adipogenesis. Evidence will be provided that CK2 regulates these processes at multiple levels. This suggests that its pharmacological inhibition combined with dietary restrictions and/or inhibitors of metabolic targets could represent an effective way to undermine the dependency of cancer cells on lipids to interfere with tumor progression.